Rheological properties of tin oxide suspensions - Santos, Iêda Maria Garcia dos; Souza, Antônio Gouveia de; Sensato, Fabrício Ronil; Leite, Edson Roberto; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier, 2002)
The rheological properties of tin oxide slurries were studied experimentally and theoretically. The deflocculants used were ammonium polyacrilate (PAA) and the copolymer poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) (PVB-PVA-PVAc), in water and ethanol, respectively. The amount of deflocculant was optimized for different solid contents by means of viscosity measurements. In spite of the high stability of PVB-dispersed slurries, a high solid concentration was not obtained. On the other hand, a slurry with a 56.4 vol.% of solids was attained when PAA was used. A theoretical study of the adsorption of PAA in its dissociated (basic solution) and non-dissociated (acidic solution) forms on SnO 2 (110) is presented. This analysis was made by means of the PM3 method using a large cluster Sn 15O 28 for the surface model. The calculated adsorption energy is larger for the ionized PAA than for the non-ionized form, indicating that alkaline slurries favor PAA adsorption on the SnO 2 surface. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Adsorption; Deflocculants; Modelling-adsorption; Rheology; SnO 2; Ammonium compounds; Ethanol; Slurries; Vinyl resins; Viscosity measurement; Water; Adsorption energy; Tin compounds; adsorption; rheology; suspension; tin oxide